2008
DOI: 10.1111/j.1468-5884.2007.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verbal working memory and cumulative linguistic knowledge on reading comprehension1

Abstract: In the present study, the effects of verbal working memory (VWM) and cumulative linguistic knowledge (CLK) on reading comprehension were investigated using an individual difference approach. We examined whether VWM and CLK are distinct verbal factors and whether each has independent influences on reading comprehension. VWM was tested using the Japanese Reading Span Test (RST). CLK was assessed using information, vocabulary, and similarity subtests of the Wechsler Adult Intelligence Scale-Revised (WAIS-R), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nation, Adams, Bowyer-Crane & Snowling, 1999). Whereas this concern highlights the need to include both verbal and nonverbal working memory tasks in future studies, there is also some evidence that verbal working memory is linked to reading comprehension independent of verbal skills (Dixon, LeFevre & Twilley, 1988;Engle, Nations & Cantor, 1990;Jincho, Namiki & Mazuka, 2008). This is also consistent with Sáez (2006, 2007), arguing that working memory relates to reading comprehension independent of verbal ability because it is the central executive component of working memory (Baddeley, 1990) that underlies this relationship.…”
Section: Discussionmentioning
confidence: 58%
“…Nation, Adams, Bowyer-Crane & Snowling, 1999). Whereas this concern highlights the need to include both verbal and nonverbal working memory tasks in future studies, there is also some evidence that verbal working memory is linked to reading comprehension independent of verbal skills (Dixon, LeFevre & Twilley, 1988;Engle, Nations & Cantor, 1990;Jincho, Namiki & Mazuka, 2008). This is also consistent with Sáez (2006, 2007), arguing that working memory relates to reading comprehension independent of verbal ability because it is the central executive component of working memory (Baddeley, 1990) that underlies this relationship.…”
Section: Discussionmentioning
confidence: 58%
“…Studies of the componential nature of a proficiency construct have been undertaken quite often for reading, writing, and speaking (e.g., De Jong, Steinel, Florijn, Schoonen, & Hulstijn, 2012; Jincho, Namiki, & Mazuka, 2008; Schoonen, Hulstijn, & Bossers, 1998; Schoonen et al, 2003; Schoonen, Van Gelderen, Stoel, Hulstijn, & De Glopper, 2011; Van Gelderen et al, 2004). These studies tend to find that linguistic knowledge components as well as speed or fluency factors are associated with success in both first language (L1) and L2 reading (Van Gelderen et al, 2004), L1 and L2 writing (Schoonen et al, 2003), and L2 speaking (De Jong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Metacognitive knowledge or strategies were also found to explain success in reading (Van Gelderen et al, 2004) and writing (Schoonen et al, 2003). Jincho et al (2008) included a reading span task in their study of reading comprehension, and found that this measure predicted variance in reading beyond what was explained by vocabulary knowledge and orthographic knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal WM and its correlate the phonological loop have been shown to be implicated in a range of language tasks including vocabulary acquisition (Gathercole, Willis, Emslie, & Baddeley, 1992), reading (Jincho, Namiki, & Mazuka, 2008), and spoken language comprehension (Adams, Bourke, & Willis, 1999). The phonological loop is the subcomponent of WM that is responsible for the short term storage and maintenance of phonological information derived from both spoken and visual (i.e., text or namable images) input (Baddeley et al, 1998).…”
mentioning
confidence: 99%